Deskripsi Pola Konsumsi Minuman Sehat Pada Mahasiswa Selama Pandemi Covid-19 - Minar, Jeane Felicia Nolly; Rasmikayati, Elly (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The covid-19 pandemic has caused a shift in consumption towards healthier options, including healthy beverages. Healthy beverages are processed products made from agricultural raw materials that can provide health benefits. The purpose of this research is to describe the pattern of healthy beverage consumption among students during the covid-19 pandemic. This research used a quantitative design with a survey method. The results show that the majority of respondents were female, 22 years old, lived in boarding houses before the pandemic but returned home during the pandemic, and the majority of their allowance was between 1-3 million rupiah. The consumption patterns of students have changed during the covid-19 pandemic. The frequency of consuming sugar-free drinks 2-4 times per week increased by 4%. Students who consumed sweetened drinks 2-4 times per week decreased by 12%. Students also changed their consumption goals to improve their immunity during the covid-19 pandemic.